DNA methylation of GITR, OX40, 4-1BB, CD27, and CD40 correlates with BAP1 aberrancy and prognosis in uveal melanoma. Issue 2 (1st April 2023) - Hoffmann, Friederike; Fröhlich, Anne; Sirokay, Judith; de Vos, Luka; Zarbl, Romina; Dietrich, Jörn; Strieth, Sebastian; Landsberg, Jennifer; Dietrich, Dimo
Abstract : Uveal melanoma represents an aggressive tumor that responds mostly poorly to established melanoma treatments. Comprehensive methylation profiling of the next-generation immunotherapeutic target genes, for example, members of the tumor necrosis factor receptor superfamily, might allow for the development of companion predictive biomarkers. We have analyzed CpG sites within the immune checkpoint genes GITR, OX40, 4-1BB, CD 27, and CD40 probed by the Illumina Infinium HumanMethylation450 BeadChip in N = 80 uveal melanomas included in The Cancer Genome Atlas with regard to BAP1 aberrancy, mRNA expression, and overall survival. In all analyzed immune checkpoint genes, BAP1 aberrancy was associated with decreased CpG methylation levels. We identified specific CpG sites that significantly correlated with BAP1 aberrancy, mRNA expression levels, and overall survival. Our results suggest epigenetic regulation of the analyzed immune checkpoint genes via DNA methylation in uveal melanoma and provide rationale for methylation testing in biomarker programs in clinical trials.